(untitled) (World of finance, 2022)
Introduction. Ukraine, noting in the Constitution inevitability of the implementation of a strategic course on the acquisition of full membership in the EU and in The North Atlantic Treaty Organization, should review the budget financing of national defense. In modern realities of the military-political situation in Ukraine, the financing of the country’s defense capability is one of the priority directions of use of funds from the State Budget of Ukraine. The purpose of the article is to study and define the directions of budget financing of Ukraine in conditions of limited financial resources and armed conflict with the Russian Federation and Euro-Atlantic integration. The main task is to identify the problems of budget financing of Ukraine’s defense expenditures and the definition of the main ways to optimize budget financing of defense expenditures in the country’s Euro-Atlantic integration. Methods. The study used general and special methods, in particular - analysis and synthesis, induction and deduction, logical generalization, abstraction. The results. The peculiarities of budget financing of the national defense of Ukraine are investigated; the essence of defense expenditures as an economic category and the overall structure of defense expenditures; the analysis of expenditures from the State Budget for defense; the amount of monetary maintenance of servicemen in Ukraine and the dynamics of its changes in recent years is calculated; the main problems of financing expenditures for national defense and ways of solving them are presented, the main ways of improving budget financing of expenditures for national defense in Ukraine are highlighted. Conclusions. It is established that the main measures to optimize the financing of national defense of Ukraine in the conditions of Euro-Atlantic integration are: ensuring the proper level of monetary support of servicemen; increase in defense sector financing; changing the structure of expenditures for national defense in accordance with NATO standards; introduction of long-term planning tools in the process of formation of the defense budget of Ukraine’s defense expenditures.